Urban solid waste management in the state Passo Baguala District of the City of Ambon - Ponto, Iriane S. (International research journal of management, IT and social sciences, 2021)
This study aims to study and analyze to reveal data and information related to whether or not the optimal handling of waste in Passo Village, Baguala District, Ambon City. For this reason, the method used in this study is research with quantitative data analysis techniques using a Likert scale. The results of the analysis using the Likert scale percentage formula prove that the local government of Ambon City does not intensively provide socialization of Regional Regulation Number 11 of 2015 concerning Waste Management to residents, there are still limited State-Based Waste Bank Facilities for community residents, in addition to other indicators that are in the same category. The calculation results of each indicator prove this added up and then divided by 11, and the average value of the quality of the answers obtained is 1.70%. Therefore It can be concluded that the Handling of Waste in the State of Passo, Baguala District, Ambon City, especially at the Research site, is still not optimal by the Ambon City Regional Regulation because the value of 1.70% is a value that is in the Very Bad category (Score between 0%-20 %) According to the Litker Scale.